Neural network modeling and forecasting of imbalances in Ukraine's labor market under extreme conditions - Kushnerov, Oleksandr; Niesheva, Anastasiia; Shcherbachenko, Viktoriia; Sokol, Vladyslav; Amiraslanov, Khaliq (Національний технічний університет "Харківський політехнічний інститут", 2026)
The full-scale military invasion of the Russian Federation has caused unprecedented distortions in the labour market of Ukraine. These deformations are characterized by deep sectoral and territorial disproportions, which are caused by mass migration, mobilization, destruction of production, and changes in the structure of labor supply and demand. This causes an urgent need to develop tools to quantify and predict said deformations, which is essential for making informed decisions. The purpose of this research is to develop and test a complex technique based on neural network modelling (Long Short-Term. Memory – LSTM). This methodology aims to identify, assess, and forecast labour market deformations and imbalances in Ukraine, and includes the development of a system of criteria for their evaluation. The research methodology is based on an integrated approach that incorporates time series analysis, neural network forecasting (LSTM), methods for detecting structural shifts and anomalies (Isolation Forest), cluster analysis (K-Means), and determination of influencing factors (Random Forest). The research presents a developed system of criteria for assessing war-induced deformations, conducts a quantitative evaluation of sectoral disruptions resulting from the conflict, provides a forecast of imbalance dynamics, and identifies the most vulnerable sectors of the economy.

Повномасштабне військове вторгнення Російської Федерації спричинило безпрецедентні деформації на ринку праці України. Ці деформації характеризуються глибокими галузевими та територіальними диспропорціями, які зумовлені масовою міграцією, мобілізацією, руйнуванням виробництв та зміною структури попиту і пропозиції робочої сили. Це викликає нагальну потребу в розробці інструментів для кількісної оцінки та прогнозування зазначених деформацій, що є важливим для прийняття обґрунтованих рішень. Метою цього дослідження є розробка й апробація комплексної методики, заснованої на нейромережевому моделюванні (Long Short-Term Memory – LSTM). Ця методика спрямована на ідентифікацію, оцінку та прогнозування воєнних деформацій і диспропорцій на ринку праці України, а також включає розробку системи критеріїв для їхньої оцінки. Методологія дослідження базується на інтегрованому підході, що охоплює аналіз часових рядів, нейромережеве прогнозування (LSTM), методи виявлення структурних зсувів та аномалій (Isolation Forest), кластерний аналіз (K-Means) і визначення факторів впливу (Random Forest). У результаті дослідження представлено розроблену систему критеріїв для оцінки воєнних деформацій, здійснено кількісну оцінку галузевих деформацій, спричинених війною, надано прогноз динаміки диспропорцій та ідентифіковано найбільш вразливі галузі.
Нейромережеве моделювання та прогнозування диспропорцій на ринку праці України в екстремальних умовах
Keywords: labour market; war deformations; disproportions; neural network modelling; LSTM; forecasting; industry analysis; structural shifts; cluster analysis; influencing factors; system of criteria; ринок праці; воєнні деформації; диспропорції; нейромережеве моделювання; галузевий аналіз; структурні зрушення; кластерний аналіз; фактори впливу; система критеріїв